Surgical treatment with bone graft in alveolar fissures of patients operated on cleft lip and palate: review of the literature - Campos Arenas, Carlos (2019)
The cleft lip and palate (FLAP) are considered as anatomical defects of deep aesthetic as well as functional impact which leads to a series of physical, functional and psychological sequelae. Within the extensive multidisciplinary treatment that patients undergo, the secondary alveolar graft is fundamental to resolve different sequelae such as anatomical defect, function and the search to continue with the proper development of the patient. The objective of this research is to review the extensive literature that exists between the parameters and considerations of this surgical technique, since there is great controversy among the various studies. The secondary alveolar graft is commonly performed between 9 and 12 years of age during mixed dentition and before the eruption of the permanent canine. According to the literature, autologous spongy bone presents the best results for this type of procedure, due to its different biological mechanisms for bone integration. The most commonly used donor site continues to be the iliac crest due to its high availability of spongy and cortical tissue, together with its low morbidity. Nowadays, secondary bone grafts have a high success rate and a reasonable reabsorption, being the most effective treatment for alveolar fissures.